2014
DOI: 10.1371/journal.pone.0101270
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Cardiac Function and Activation of Anti-Inflammatory Vasoactive Peptides Expression in the Rat Myocardium by Low Level Laser Therapy

Abstract: Low-level laser therapy (LLLT) has been used as an anti-inflammatory treatment in several disease conditions, even when inflammation is a secondary consequence, such as in myocardial infarction (MI). However, the mechanism by which LLLT is able to protect the remaining myocardium remains unclear. The present study tested the hypothesis that LLLT reduces inflammation after acute MI in female rats and ameliorates cardiac function. The potential participation of the Renin-Angiotensin System (RAS) and Kallikrein-K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 68 publications
5
42
1
4
Order By: Relevance
“…Several extracellular matrix genes take part of the cardiac remodeling after MI. In tune with earlier reports (Roy et al, 2006; Manchini et al, 2014), mRNA modifications regarding to cardiac remodeling were observed in our experimental groups. mRNA expression analysis revealed significant upregulation of most genes after both occlusion and ablation compared to control.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Several extracellular matrix genes take part of the cardiac remodeling after MI. In tune with earlier reports (Roy et al, 2006; Manchini et al, 2014), mRNA modifications regarding to cardiac remodeling were observed in our experimental groups. mRNA expression analysis revealed significant upregulation of most genes after both occlusion and ablation compared to control.…”
Section: Discussionsupporting
confidence: 93%
“…Upregulation of all these mRNAs after MI procedures could be due to an establishment of a secondary inflammation that accomplishes MI by necrosis and other cell death mechanisms as reported by earlier studies (Manchini et al, 2014; Saxena et al, 2016). Importantly, inflammation mediator expressions were mostly unaltered when occlusion and ablation were compared, indicating the same activation pathways, there was an increased mRNA expression of most interleukin analyzed in both procedures when compared to control.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Depending on the wavelength, dosage, and condition of the irradiated tissue, the laser can induce an anti-inflammatory effect, reducing pain, and accelerating cell proliferation (Manchini et al 2014). Based on a special mechanism of electromagnetic emission, LLLI may increase cellular metabolism and improve structural characteristics, which has been proven effective in different cell types (AlGhamdi et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of the RV outflow tract were obtained from the parasternal short-axis view at the level of the aortic valve during end-diastole (Egemnazarov et al, 2015). We included only animals with pressure gradients between 25–55 mmHg (Manchini et al, 2014). The diastolic (RVDA) and systolic (RVSA) transverse areas of the RV were measured at the basal, middle, and apical view.…”
Section: Methodsmentioning
confidence: 99%